The efficacy of a chicken antibody for the development of immunoassay‐based rapid detection in sugarcane mosaic virus disease - Widhi Dyah Sawitri; Retnosari Apriasti; Agus Heri Setyo Wahyudi; Putri Andreyna Saragi; Victorin Mega Putri; Sugiharto Sugiharto; Win Darmanto; Nurmalasari Darsono (Universitas Gadjah Mada, 2023)
Sugarcane Mosaic Virus (SCMV) infection is one of the most serious problems that can result in severe yield loss of sugarcane. Since the symptoms of SCMV infection are similar to other biotic and abiotic stress symptoms, the development of a rapid diagnostic with high precision is required. The use of laboratory animals such as rabbits is required for antibody production in immunoassay‐based detection. However, due to its many advantages, specific chicken egg yolk immunoglobulin (IgY) has received considerable attention as an alternative antibody production in immunodiagnostics for infectious diseases. In this study, IgY antibody against SCMV recombinant coat protein (CP) was successfully obtained from chicken blood serum and tested to compare its efficacy against antibody from rabbit (IgG) using immunocapture reverse transcription‐polymerase chain reaction (IC‐RT‐PCR). The result showed that IgY and IgG could detect 0.1 g SCMV infected leaves using 1000‐times‐diluted antibodies. The IgY antibody was also confirmed to be reproducible and potentially applicable in plant disease diagnostics using an antibody‐based detection.